Hukum Tajam Ke Bawah Tumpul Ke Atas (Perspektif Sosiologis Penegakan Hukum di Indonesia) - Irwan, Irwan; Wira Perdana, Fadjrin; Lumban Tungkup, Doharman; Miran, Miran; Suteki, Suteki (CV. Publikasi Indonesia, 2022)
Weak law enforcement and equitable development as well as other discriminatory treatments still occur in the implementation of minority rights in Indonesia. The purpose of this research is to examine law enforcement